FORMULATION AND OPTIMIZATION OF CAFFEINE NANOEMULSION USING FACTORIAL DESIGN STUDY - Bannan Muthi’atul Af-idah; Dwi Nurahmanto; Dessy Dwi Risky (UPT Penerbitan Universitas Jember)
Caffeine was an alkaloid commonly used as activeingredient in cosmetics due to its high biologicalactivity for skin health as anticelulit, sunscreen,antioxidant, and photoaging inhibitor [6]. Caffeinehad potential antioxidant properties that couldprotect cells against the UV radiation inducecarcinogenesis with stimulatory effect on apoptosisin the UVB-treated epidermis cell in mice skin [8].High hidrophilic properties of caffeine (log P = -0.07)caused difficulties to penetrate through the stratumcorneum of human skin [9]. Nanoemulsion was adrug delivery system that had good stability andcould potentially increase penetration of the drugthrough the skin that had particle size approximately1 – 100 nm. Oil phase, aqueous phases, andsurfactant are basic component of nanoemulsion[11]. Surfactant was the important compound inpreparation of nanoemulsion. Type, amount ofsurfactant, and HLB value of surfactant can influencenanoemulsion stability [1]. Isopropyl miristate (IPM)was chemical penetration enhancer (CPE), wasadded in skin drug formulation to incrase thepenetration ability of the drug [3]. This study aimedto investigate the effect of hydrophile lipophilebalance (HLB) value of surfactant combination(tween 80 and span 80) and IPM concentration onthe stability and penetration ability of nanoemulsionusing factorial design method and obtain theoptimum formula of caffeine nanoemulsion usingDesign Expert 9.0 analysis.